Unravelling the miniscule size effect of auxiliary donor in D-D-π-A type dipolar photosensitizers on quasi-solid state DSSC performance. (February 2021) - Kumar, Chitra; Raheem, Abbasriyaludeen Abdul; Mohan, Ramesh; Shanmugam, Ramasamy; Praveen, Chandrasekar
Abstract: Three new dipolar organic dyes of the type D-D-π-A were constructed on fluorenothiophene backbone by varying the terminal donor auxiliary such as -NMe2, -NEt2 and -NPh2 . The effect of such structural variation on the photophysical and electrochemical properties has been investigated. Computational studies obtained from DFT/TD-DFT calculations were found to be in good correlation with the experimental optoelectronic results. TiO2 based n-type quasi-solid state DSSCs constructed on the synthesized dyes revealed a gradual increase in photovoltaic performance with increase in donor size. The trend in power conversion efficiency (η) was found to be -NPh2 (4.10%) > -NEt2 (3.44%) > -NMe2 (2.57%). Electrochemical impedence analysis also confirmed the longer electron life time for dye possessing bulky -NPh2 groups in comparision to -NEt2 and -NMe2 groups, thus demonstrating the impact of increased donor size on the DSSC performance. Overall, this paper validates the impact of donor size on the DSSC performance and could inspire the selection of appropriate auxiliary donors to enhance the efficiency in futuristic endeavors. Highlights: The donor size of three dyes (FMD, FED, FPD) was systematically varied by groups such as -NMe2, -NEt2 and -NPh2 to investigate their effect the on the optoelectronic properties and quasi-state DSSC performance. This minute variation of donor size suggests that the dye possessing a bulky -NPh2 group exhibits better optical (molar absorptivity and band gap) and electrochemical (HOMO-LUMO) properties to match the requirements for DSSC. The experimental photophysical and electrochemical results correlated well with DFT calculations. Computed quantum chemical properties and other molecular parameters were found to be in favour of FPD as better dye candidate. The better physical and chemical properties of FPD was reflected in the photovoltaic performance of prototype DSSC devices, which revealed a power conversion efficiency in the order of FPD (4.10%) > FED (3.44%) > FMD (2.57%) in gel based electrolyte. Our results showed that sterics and electronics of donor group are key to control the optoelectronic properties of push-pull dyes.